Does market mechanism promote online/mobile information disclosure? Evidence from A-share companies on Shenzhen Exchange Market. (2014) - Bai, Yunxia; Yan, Mengying; Yu, Feng; Yang, Jiaqin
As online and mobile communications have been rapidly growing in China, internet has become an important channel for investors to be exposed to information disclosed by listed firms. Contrary to previous research, we argue that a certain online/mobile information disclosure level may have different influence on the firm value in terms of different corporate performance levels. This conclusion is supported by the empirical evidence collected from A-share companies listed on Shenzhen Exchange (China) in 2011. It is found that companies with lower performance levels have strong motives to disclose less information to avoid the potential discount of the firm value. As a result, more strict supervisions from the regulatory agencies are called for since market mechanism fails to protect investors.